Encouraging Entrepreneurial Spirit in Generation Z through Digital Marketing (Tiket10.Com) Education and Training - Jualiater Simarmata; Astri Rumondang B.; Dian C. Anggara; Gratia Atanka Barus; Andre Yosafat (Didaktika: Jurnal Kependidikan, 2024)
Digital marketing-based entrepreneurship training is an effort to prepare Generation Z to enter the digital business world by utilizing digital Tiket10.Com platforms. The focus of this training is to teach skills for Generation Z such as online marketing, inventory management, and customer service. Trainees will be guided in understanding digital marketing and effective marketing strategies to increase the visibility of their products. In addition, the training also includes managing transactions safely and efficiently. Tiket10.Com, as a digital marketing company engaged in selling airline tickets, trains, telephone credits, as well as electricity and water payments, will provide deep insight into the industry. This education and training also guide participants to understand consumer behavior and the latest market trends, as well as leverage data to make smart decisions in their business. Through Tiket10.Com training, it is expected that Generation Z will be equipped with the knowledge and skills necessary to succeed in managing their own digital marketing business. This is expected to encourage economic growth in the region and open up new opportunities for independence and career development of Generation Z in the digital era.